GENDER-SENSITIVE CORRELATION BETWEEN COMMUNICATION AND ORGANIZATIONAL SKILLS WITH PROFESSIONAL EFFECTIVENESS OF MANAGERS - N V Obidina (Peoples' Friendship University of Russia (RUDN University), 2016)
The paper discusses the problem of gender-sensitive correlation between the communicative and organizational skills and the professional performance of managers in commercial organization. The topicality of research is preconditioned by the fact that today an increasing number of women get the senior positions in business in Russia. The article submits and analyses the results of the empirical research that took place in a commercial organization (managers of clothes and accessories retail shops). Store managers of this organization took part in the research, including 82 male and 231 female. The age of the respondents ranged from 21 to 42 years old. The work experience of the managers was no less than one year. The communicative and organizational skills were measured with the help of the test-questionnaire "Communication and organizational skills" (COS) worked out by V.V. Sinyavsky and B.A. Fedorishin. The professional effectiveness was determined by two indicators: 1) the implementation of shop sales plan in 2014 and in 2015, 2) the results of expert estimates obtained using the feedback from "360 Degrees". The results of correlation analysis demonstrated the strong relations between the manifestation of communicative and organizational skills and the indicators of professional effectiveness, received by using the feedback from "360 Degrees" in both male and female groups of respondents. At the same time, the implementation of shop sales plan in 2014 also showed a strong positive relationship with organizational and communicative skills especially in female group. By the end of 2015, after the financial crisis, these relations were although preserved, but getting weaker.